Influence of Age, Gender, and Other Intrinsic Factors on Portuguese Family Farmers’ Motivations for Short-Term Continuity - Dinis Isabel (European Countryside)
This study investigates the intrinsic factors influencing Portuguese family farmers’ motivations for short-term continuity, utilizing data from the Agricultural Censuses. The research, based on five Beta regression models, highlights the significance of socio-demographic characteristics, such as age, gender, and education, alongside farm structures and agricultural practices in shaping decisions to sustain farming. Results reveal diverse motivational frameworks, including economic viability, supplementary income, emotional attachment, and the lack of professional alternatives. The findings offer valuable insights for policymakers aiming to balance economic incentives with cultural preservation in agricultural policy.